PENGEMBANGAN E-MODUL PADA MATERI SISTEM REPRODUKSI UNTUK SISWA KELAS XI SEKOLAH MENENGAH ATAS - Fadilah Emiliana (BEST Journal (Biology Education, Sains and Technology), 2023)
This research was carried out with the aim of developing valid and practical e-modules on reproductive system material for class XI in high school (SMA). The research conducted is a type of research that aims to develop using the ADDIE model, which includes analysis, design, development, implementation, and evaluation. At the analysis stage, an analysis of the needs of the e-module, an analysis of the characteristics of the students, an analysis of the material, and an analysis of the availability of infrastructure were carried out. The design stage involves designing the appearance and material structure of the e-module. The development stage involves the development of design results in the form of e-modules. The implementation stage is the practicality test stage of the e-module for 98 students of class XI SMA and 9 biology teachers in SMA districts Banyumas, Cilacap, and Purbalingga. The evaluation stage is carried out to test the validity of the e-module by material and media experts. how to distribute a questionnaire and use a closed questionnaire instrument with a Likert scale. The data were analyzed using quantitative descriptive data analysis techniques. The results showed that the e-module validity test for reproductive system material for class XI high school, according to the material experts, achieved a score of 3.72 (in the category suitable for use), and the media experts obtained a score of 3.72 (in the category very suitable for use). The results of the e-module practicality test by the biology teacher obtained an average result of 3.50 (very feasible to use), and the students obtained an average result of 3.37 (very good). The conclusion in this study is that the development of e-modules on reproductive system material is valid and practical, so it is suitable for use in biology learning on reproductive system material. Therefore, it is necessary to carry out further research to determine the effectiveness of the e-module in the implementation of biology learning in the reproductive system material for senior high schools.